2021
DOI: 10.3389/fpls.2021.708370
|View full text |Cite
|
Sign up to set email alerts
|

The Algal Chloroplast as a Testbed for Synthetic Biology Designs Aimed at Radically Rewiring Plant Metabolism

Abstract: Sustainable and economically viable support for an ever-increasing global population requires a paradigm shift in agricultural productivity, including the application of biotechnology to generate future crop plants. Current genetic engineering approaches aimed at enhancing the photosynthetic efficiency or composition of the harvested tissues involve relatively simple manipulations of endogenous metabolism. However, radical rewiring of central metabolism using new-to-nature pathways, so-called “synthetic metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 155 publications
0
17
0
Order By: Relevance
“…[44] The algal chloroplast, specifically that of C. reinhardtii, is well suited for genetic engineering and there is an increasing emphasis on the application of synthetic biology. [11,12,5,9] Many of these approaches are reliant on the ability to perform a series of plastome edits to the same cell line. However, conventional strategies for selection of transformants largely preclude this: methods based on photosynthetic restoration are restricted to a particular mutant host and specific locus, and can only be performed once, [41] whilst portable markers for engineering WT plastomes are currently limited to just three and these also operate on a single-use basis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[44] The algal chloroplast, specifically that of C. reinhardtii, is well suited for genetic engineering and there is an increasing emphasis on the application of synthetic biology. [11,12,5,9] Many of these approaches are reliant on the ability to perform a series of plastome edits to the same cell line. However, conventional strategies for selection of transformants largely preclude this: methods based on photosynthetic restoration are restricted to a particular mutant host and specific locus, and can only be performed once, [41] whilst portable markers for engineering WT plastomes are currently limited to just three and these also operate on a single-use basis.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] An ever-growing 'chloroplast toolkit' for C. reinhardtii now allows routine insertion of codon-optimized transgenes into the plastome, and their high-level and regulated expression. [9] More recently, there has been a growing emphasis on the utilization of synthetic biology (SynBio) approaches to chloroplast engineering. [10][11][12]5] This has been supported by the availability of robust, well annotated genomic and transcriptomic data for the C. reinhardtii plastome [13,14] and the emergence of standardized DNA assembly methods for rapid and highthroughput design and construction of transgenes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to engineer photosynthesis are limited by available technologies, particularly for stable nuclear transformation of large, multigene constructs (>10 genes) into nuclear genomes ( Ort et al, 2015 ) and for the transformation of chloroplast genomes ( Bock, 2015 ; Jackson et al, 2021 ). However, introduction of point mutations to plastome-localised RbcL via a restriction enzyme-based system has been re-demonstrated with a 40% editing efficiency ( Lin et al, 2021 ).…”
Section: A Year At the Forefront Of Engineering Photosynthesismentioning
confidence: 99%
“…To this end, microalgae represent an attractive biotechnology platform for the synthesis of recombinant proteins [24][25][26] . The advantages of using microalgae as opposed to traditional heterotrophic platforms of Escherichia coli, yeast, or CHO cells are: (i) the low-cost phototrophic cultivation of the alga in sterile, controlled photobioreactors using simple and inexpensive medium 27 ; (ii) the generally recognized as safe (GRAS) status of a number of algal species, including the chlorophyte Chlamydomonas reinhardtii 28 ; (iii) the availability of the chloroplast as a unique biosynthetic and storage compartment within the cell that contains its own minimal genetic system [29][30][31] ; and (iv) a growing interest and adoption of enabling synthetic biology principles for creating bespoke cell factories using microalgae 32 . Whilst several recent studies have reported the production of PETase in microalgal species through nuclear engineering 33,34 , the use of the chloroplast for expression of foreign genes confers several bene ts.…”
Section: Introductionmentioning
confidence: 99%